Satisfaction of Undergraduates with Library and Information Science Course and Some Factors that Influence their Choice of the Programme - Umeozor, Susan Nnadozie (International Journal of Knowledge Content Development & Technology, 2022)
This study was conducted to assess the level of satisfaction of undergraduates with the Library and Information Science (LIS) course and some of the factors that influence their choice of the programme. The population of the study was all the 400 level undergraduates in the Department of Library and Information Science, Faculty of Education, University of Port Harcourt. A structured questionnaire, made up of three parts, was utilized for data collection. The first part involved the level of satisfaction of the respondents with the LIS programme while the second and third parts involved the influence of parents and peers on the respondents’ choice of LIS programme, respectively. Out of the 21 copies of the questionnaire distributed, 20 were retrieved indicating a 95.2% response rate with 75% (15) male and 25% (5) female. Data were analyzed using percentages and simple regression analysis. Results indicated that the respondents were highly satisfied with the choice of LIS programme and would recommend the programme to others. Parental influence on the respondents’ choice of LIS programme was minimal accounting for 7.8% of the changes in the choice of the programme while peer influence on the respondents’ choice of the programme was substantial accounting for 78.0% of the changes in the choice of the programme. The fact that the respondents were satisfied with their choice of career in LIS is a strong indication that they would be committed to providing excellent service in librarianship needed to cater for the mutated information requirements of the society.